Burden of hypertension in Ghana – Analysis of awareness and screening campaign in the Ashanti Region of Ghana. (January 2022) - Tannor, Elliot Koranteng; Nyarko, Obed Ofori; Adu-Boakye, Yaw; Owusu Konadu, Saabea; Opoku, Gilda; Ankobea-Kokroe, Frank; Opare Addo, Mercy; Amuzu, Evans Xorse; Ansah, Gilgal Justice; Appiah-Boateng, Kate; Ansong, Daniel
Objectives: Hypertension is a major risk factor for cardiovascular mortality globally and in Ghana. May Measurement Month (MMM) is a global awareness and screening campaign initiated by the International Society of Hypertension. Methods: Participants were recruited by opportunist sampling in the Ashanti region of Ghana. The blood pressures of participants were measured three times and the mean of the last two readings was used for the analysis. Simple and multiple logistic regression was used to determine the predictors of hypertension. Results: The MMM 2018 awareness and screening campaign enrolled 5054 participants with a mean age of 39.4 ± 14.7 years. There were 2553 (50.6%) males, 987 (20.1%) of respondents had never checked their blood pressure and 676 (13.9%) had a prior history of hypertension. The prevalence of hypertension was 37.4%. We found that 589(66.8%) of 822 respondents with high blood pressure did not have a history of hypertension. Respondents with a known history of hypertension on medication were 442 (65.9%) and 219(68.0%) of 322 respondents on medication had uncontrolled hypertension. The predictors of high blood pressure in a multiple logistic regression were increasing age (OR = 1.05 CI 1.05–1.06, p < 0.001), history of alcohol intake (OR = 1.33 CI 1.04 −1.70, p = 0.02), overweight (OR = 1.4 CI 1.14–1.76, p = 0.001) and obesity (OR = 1.32, CI 1.01–1.74, p = 0.047). Conclusion: There is a high prevalence of hypertension in the Ashanti region in Ghana. Most participants with hypertension were not aware and the majority of those with hypertension on medications were uncontrolled. This calls for more education and screening of hypertension to decrease cardiovascular mortality.